ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA AKUNTANSI DALAM PEMILIHAN KARIR SEBAGAI AKUNTAN PUBLIK - Imaniah, Nur; Purba , Mortigor Afrizal (SCIENTIA JOURNAL, 2023)
This study aims to examine the effect of financial rewards or salary, work environment, professional training, professional recognition, and social values on the interest of accounting students in choosing a career to become a public accountant. This research method is a purposive sample technique. This research technique was conducted by distributing questionnaires to accounting students in Batam City. Data analysis using IBM SPSS 22.00 application. The results of this study are that financial rewards and work environment have a positive effect on the interest of accounting students in decide a career as a public accountant. Meanwhile, professional training, professional recognition and social values have no significant effect. Keyword: Financial rewards, work environmental,professional training,professional recognitionan, social value